ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN OUTSOURCING D BIDANG PUBLIC AREA PADA PANGERAN BEACH HOTEL PADANG - King, Masber Don; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Indonesia is an archipelagic country that has its own natural beauty, one of which is the province of West Sumatra. West Sumatra's leading tourism sector includes natural beauty, culinary and hospitality. West Sumatra is located on the west coast in the central part of the island of Sumatra which borders the provinces of North Sumatra, Riau, Jambi and Bengkulu. One of the areas visited by tourists is the city of Padang. Prince Beach Hotel is located at Jl. Ir. H Juada No. 79, Flamboyan Baru, West Padang District, Padang City, West Sumatra 25115. The Pengeran Beach Padang Hotel is very strategically located in the center of Padang city so it is a very popular hotel in the city of Padang and has many fans. The aim of this research is to find out what factors influence the performance of outsourced employees in the public area at Pangeran Beach Hotel Padang. The public area workforce at Pangeran Beach Hotel Padang does not use its own workforce but instead uses additional workforce from outside (Outsourcing). Outsourcing is the use of labor from third parties to complete certain jobs within the company. This research method uses a qualitative method with a descriptive approach. The results of this research are that the factors that influence the performance of outsourced employees have several important indicators in them, namely personal factors, leadership factors, team factors, system factors and situational factors. Keywords: Performance, employees, outsourcing, public area, Pangeran Beach Hotel Padang